DESIGN OF EXTRACTION PROCESS WITH INTERACTIVE GRAPHICAL PROGRAMMING - Uysal, Umut; Oner, Mualla (YILDIZ TECHNICAL UNIV, 2006)
In this work, Lqd_Ext 1.0 program was developed by using Visual Basic. net platform to solve liquid-liquid extraction problems in separation processes. Triangular diagram graphical solution technique for liquid liquid system has been used and numerically calculated results have been given for crosscurrent and countercurrent multistage extraction design. The problems have been given by using five different systems for crosscurrent and countercurrent methods. Lqd_Ext 1.0 program can find stage requirements, the composition of the extract and raffinate phases after each stage, flow rates for all streams leaving from the equipment.
Keywords: Liquid-liquid extraction; graphical solution; multistage extraction; interactive computer programming; Engineering